2014
DOI: 10.1007/s10237-014-0563-y
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of blood flow and pressure drop in the pulmonary arterial and venous circulation

Abstract: A novel multiscale mathematical and computational model of the pulmonary circulation is presented and used to analyse both arterial and venous pressure and flow. This work is a major advance over previous studies by Olufsen and coworkers (Ottesen et al., 2003; Olufsen et al., 2012) which only considered the arterial circulation. For the first three generations of vessels within the pulmonary circulation, geometry is specified from patient-specific measurements obtained using magnetic resonance imaging (MRI). B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
142
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(147 citation statements)
references
References 64 publications
4
142
1
Order By: Relevance
“…Moreover, contrary to Hess & Murray's result of an inverse scaling of the pressure gradient in successive branchings with δ (∆p/L = δ´1, see Equation (4)), radius-dependent slenderness factors are found experimentally: L/r = 15.75r 1.10 for arterioles with r ě 50 µm, 1.79r 0.47 for arterioles with r ď 50 µm, 14.54r for veins with r ď 2000 µm, [12,13]. Notice that the fundamental deviation of Huang's results [12] from the H-M law depend also on the different ordering of "successive branches" adopted therein, whose classification cannot be directly extended to capillary networks.…”
Section: A Brief Summary Of Experimental Results and Of Other Allometcontrasting
confidence: 45%
“…Moreover, contrary to Hess & Murray's result of an inverse scaling of the pressure gradient in successive branchings with δ (∆p/L = δ´1, see Equation (4)), radius-dependent slenderness factors are found experimentally: L/r = 15.75r 1.10 for arterioles with r ě 50 µm, 1.79r 0.47 for arterioles with r ď 50 µm, 14.54r for veins with r ď 2000 µm, [12,13]. Notice that the fundamental deviation of Huang's results [12] from the H-M law depend also on the different ordering of "successive branches" adopted therein, whose classification cannot be directly extended to capillary networks.…”
Section: A Brief Summary Of Experimental Results and Of Other Allometcontrasting
confidence: 45%
“…Their results indicated that central aortic shunts of longer length and with angulations were easy to get clotted. Although there are a few studies on hemodynamics of coronary artery bypass grafts 13 and pulmonary arterial blood flow, 14 little attention was given to the simulation of small arteries, such as the radial artery and the dorsalis pedis artery. The method of radial artery point has been used by Chinese medicine for thousands of years, to obtain more information about human body and some diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Starting with the model expanded to total lung capacity, the distribution of P e is calculated at each airway and acinus. Equation (A 11) is solved for the pressure drop along the airways, starting at the model periphery with P d as a boundary condition and assuming total (lung) expiratory flow rate of 0.01 l s 21 . Solution then progresses through the airways towards the trachea.…”
Section: Simulation Of Forced Expiration In Explicitly Branched Treesmentioning
confidence: 99%
“…Sites of flow limitation are identified (defined as U greater than 99% of c), and the flows in a limited airway and all of its subtended airways are held fixed over the time interval for computation (taken here as 0.05 s). The total expiratory flow is incremented in steps of 0.01 l s 21 and pressure drop in all non-limited airways recomputed, until the maximal flow for the current geometry is reached. Lung volume is then decreased by the computed expired volume, P e is recomputed, and the process repeated.…”
Section: Simulation Of Forced Expiration In Explicitly Branched Treesmentioning
confidence: 99%